PENINGKATAN KINERJA PEMERINTAH DAERAH MELALUI E-GOVERNANCE BERBASIS SUMBER DAYA MANUSIA STRATEGIK (STUDI KASUS DI PEMERINTAH KABUPATEN DEMAK) - Edy Suprianto (Jurnal Akuntansi Indonesia, 2015)
This research tries to analyze the performance effectiveness and efficiency of Demak district government through the implementation of good governance with the support of information technology and human resource management strategic. This research tries to incorporate research conducted by Edy (2013) on the effect of good governance, information technology and strategic human resource management on the performance of local governments in Demak and Edy (2014) on the effects of commitment, executive capability, financial and legislativesupport to information technology. The population of this research is the entire work unit region (SKPD) in Demak as many as 28 SKPDs with the unit of analysis of the head of SKPD as policy maker. Samples are selected by using census method so that all SKPDs have the opportunity to be selected as sample. The analysis is administered byusing qualitative analysis method of FGD (Focus Group Discussion) and in-depth interviews, secondary data analysis, and literature. It also uses quantitative analysis with PLS analysis tools. From 28 SKPDs in Demak district government, only 10 SKPDs that can be interviewed and 60 samples who answered the questionnaire. Based on the hypotheses test results, it is concluded that good governance, information technology and strategic human resource management positively influence the performance of local governments. The research by Edy (2014) on the effects of commitment, executive, financial and legislative support for information technology also positively influence the performance of government.